MODEL OF ECONOMIC EMPOWERMENT OF WOMEN THROUGH UPZ - Hilyati Inayah; Yusnita Yusnita; Fitri Yani (International Journal Reglement & Society (IJRS), 2021)
This study aims to describe and analyze the economic empowerment program carried out for women through Zakat Collection Unit (UPZ/Unit Pengumpul Zakat). This research is a field research with a descriptive approach. Primary data sources were obtained by conducting interviews with participants consisting of UPZ managers and fostered participants from women. Secondary sources are obtained from zakat management regulations and several relevant articles. The results of this study prove that empowerment through zakat funds managed by UPZ in the form of revolving loans by requiring Shalat Shubuh (Shubuh prayers ) is an effective and efficient model to implement. This study recommends that all mosques establish UPZ and carry out economic empowerment using zakat funds.